Meningkatkan Kinerja Karyawan Melalui Sistim Informasi Manajemen dan Komunikasi (Studi pada Biro Pengelolaan Barang Milik Daerah Setda Provinsi Jambi) - Gupron Gupron (J-MAS (Jurnal Manajemen dan Sains), 2019)
This study aims to analyze the effect of Management Information Systems and Communication on the performance of employees both partially and simultaneously at the Regional Secretariat's Regional Management Bureau of Jambi Province. The population in this study were employees of the Regional Secretariat Regional Management Bureau of Jambi Province with a number of 77. Because the population in this study was less than 100 people, in this study the sampling method used the census method. Quantitative analysis method using Path Analysis, followed by analysis of determination (R Square), partial hypothesis testing (t test) and simultaneous (F test) with alpha 5 percent (0.05). Before further analysis, the classical assumption test is carried out first. Analysis tools using SPSS version 21.0 for Windows. The results showed that management and communication information systems had a positive and significant effect on the performance of employees at the Regional Secretariat's Regional Management Bureau of Jambi Province.